Oryzaball (Riceball) / Nor Hafizah Mazlan ... [et al.] - Mazlan, Nor Hafizah; Azmi, Farhan; Sulaiman, Suria; Tarmazi, Siti Anis Adilah (2022)
Traditional food is the heart of our heritage. Every state, every race and tribe have their own culture and heritage that they take pride of. For Malaysian, Nasi (rice) is staple food, and there are varieties of nasi dishes such as nasi dagang, nasi kerabu, nasi lemuni, nasi lemak, nasi minyak, nasi tomato. Each nasi has their own uniqueness that comes from the ingredients. For example, Nasi Lemuni uses Lemuni leaves, and Nasi Kerabu is popular for its blue color which comes from a blue flower known as Bunga Telang. OryzaBall recreates the taste of the three nasi (rice) that are loved by the Malaysians named nasi dagang, nasi kerabu and nasi lemuni with fillings at the center in one packaging. This savory product is produced from the original Malaysian ingredients with a touch of Italian dishes called arancini. It is created to let people taste the three types of nasi in a packaging in one go. It is packed in paper container to make reheating in microwave or frying easy, people can have all three types of nasi wherever and whenever they want. OryzaBall is expected to promote local delicacies worldwide in a form that everyone can enjoy. The product also has longer shelf life and is easier to export to other countries, which is an advantage.